(untitled) (American Journal of Islam and Society, 1986)
Introduction The Islamic canons on news are deeply rooted in divine inspiration, whereas Western or Western-influenced laws and regulations are usually products of human organhtions and individuals. Sandman, Rubin, and Sachsman classified the restrictions controlling news under: self-control, internal control, monopoly control, advertiser control, source control, and government or public control. Islamic guidelines are derived specifically from the divine revelation received by the Prophet of Islam, Muhammad (PBUH), fourteen centuries ago. Muslims believe that the Creator knows best about human nature. Therefore only He can provide His creatures with the most appropriate guidance to attain felicity both in this life and the next.‘ Since the Prophet Muhammad is the seal of the divine messenger, however, one may wonder how guidance revealed fourteen centuries ago could survive all the changes occuring since its revelation. In fact, although the Holy Qur’an and the Sunnah cover all aspects of life, they are not confined to rigid details nor, except in a few areas, do they prohibit interpretation. These matters are generally regarded, from the Islamic viewpoint, as critical decisions for the welfare of human beings regardless of where or when they live. Examples of these matters are capital punishment, adultery, and theft. Even in these cases, the Holy Qur’an and the Sunnah do not lay out detailed jurisdictional prescriptions for implementation. Jurisdiction and procedure are left to the judge, whose responsibility is to ...